Ferromagnetic‐Based Charge‐Accumulation Triboelectric Nanogenerator With Ultrahigh Surface Charge Density. Issue 31 (5th July 2022) - Qi, Youchao; Liu, Guoxu; Bu, Tianzhao; Zeng, Jianhua; Zhang, Zhi; Zhang, Chi
Abstract: An encouraging micro‐energy harvesting technology, the triboelectric nanogenerator (TENG), has been proven to transfer ambient environmental micro‐energy into electricity, but a low surface charge density results in low performance and limits the practical application of TENG. Here, a ferromagnetic‐based charge‐accumulation TENG (FC–TENG) is proposed with ultrahigh surface charge density and performances. The FC–TENG introduces a ferromagnetic media to enhance the output charge by magnetization effect. Meanwhile, the charge can also be continuously accumulated by the charge pump effects. Based on these two effects, an ultra‐high surface charge density of 2.85 mC m −2 is obtained under ambient atmospheric conditions using an ultra‐thin PET film (3 µm) and deposited Permalloy ferromagnetic electrodes. Meanwhile, the surface charge density of the FC–TENG can always maintain more than 1.5 mC m −2, even if the relative humidity arrives at 90%. This work provides a prospective technical mode to enhance the surface charge density of TENG, which would shed a new insight and guidance on the high‐performance TENG for various environmental conditions such as the ocean, industrial manufacturing, aerospace, and rail traffic. Abstract : The ferromagnetic‐based charge‐accumulation triboelectric nanogenerator introduces a ferromagnetic media to enhance the output charge by magnetization effect. Meanwhile, the charge can also be continuously accumulated by the charge pump effects. Based on both effects, an ultrahigh surface charge density up to 2.85 mC m −2 is obtained by using the 3 µm PET film and deposited Permalloy ferromagnetic electrode.